ISLAMIC ENDOGENOUS MONEY: EVIDENCE FROM THE ISLAMIC BANKING SYSTEM IN INDONESIA AND MALAYSIA - Khoirul Umam; Abdul Ghafar Ismail; Achmad Tohirin; Jaka Sriyana (Journal of Islamic Monetary Economics and Finance, 2021)
This paper proposes a theoretical model of endogenous Islamic money and empirically analyses the endogeneity of Islamic money supply under fiat and fractional reserve systems. The causal relations between Islamic money and macro and financial variables are assessed using the autoregressive distributed lag (ARDL) model and error-correction modelling (ECM). The results suggest that the greater the maturity and the larger the asset share in the Islamic financial system, the better the endogeneity of money. They also reveal that the profit and loss sharing system can connect the economy to money, minimise the exogenous potential of the fractional reserve requirement system, and eliminate the exogenous feature of the fiat money system. Accordingly, the study argues that an Islamic endogenous money system can be developed in fiat and fractional reserve banking systems.